Study on the nature of the electrochemically synthesized hard Fe-15.4 mass Ni-0.70 mass C alloy film - Haseeb, A.S. Md. Abdul; Hayashi, Y.; Masuda, M.; Arita, M. (Materials Research Society, 2003)
Electrochemical synthesis of hard Fe-15.4 mass Ni-0.70 mass C alloy film with a hardness 750 HV was carried out from sulfate-based bath containing a small amount of citric acid and L-ascorbic acid. The nature of the alloy was investigated by different characterization techniques including x-ray diffraction, x-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy, Mossbauer spectroscopy, differential scanning calorimetry, and magnetic measurements. The decomposition behavior of the alloy was also studied and compared with that of thermally prepared martensite. It was found that the electrochemically deposited Fe-Ni-C alloy exists in a state that is ahead of the freshly quenched state of martensite. It is suggested that the state of the electrochemically deposited Fe-15.4 mass Ni-0.70 mass C alloy corresponds to the state of thermal martensite, which had been heated to the preprecipitation stage of tempering.